Persisting speech errors or emerging phonological systems? - Mildner, Vesna (Array, 2010)
The aim of this study was to analyze hearing-impaired children's renditions of /š/ in words where the target sounds were /š/, /s/ and /č/, in order to discover possible systematic acoustic characteristics that may be imperceptible or neglected by listeners but reflect their emerging phonological systems. The relation between acoustic data and perception tests is discussed and the results for the children with cochlear implants and traditional hearing aids are compared.